Proof: Distributive Applied
Let's prove the following theorem:
(a + b) ⋅ (b ⋅ (-1)) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1))
Proof:
# | Claim | Reason |
---|---|---|
1 | (a + b) ⋅ (b ⋅ (-1)) = (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))) | (a + b) ⋅ (b ⋅ (-1)) = (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))) |
2 | a ⋅ (b ⋅ (-1)) = (a ⋅ b) ⋅ (-1) | a ⋅ (b ⋅ (-1)) = (a ⋅ b) ⋅ (-1) |
3 | b ⋅ (b ⋅ (-1)) = (b ⋅ b) ⋅ (-1) | b ⋅ (b ⋅ (-1)) = (b ⋅ b) ⋅ (-1) |
4 | (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1)) | if b ⋅ (b ⋅ (-1)) = (b ⋅ b) ⋅ (-1) and a ⋅ (b ⋅ (-1)) = (a ⋅ b) ⋅ (-1), then (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1)) |
5 | (a + b) ⋅ (b ⋅ (-1)) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1)) | if (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1)) and (a + b) ⋅ (b ⋅ (-1)) = (a ⋅ (b ⋅ (-1))) + (b ⋅ (b ⋅ (-1))), then (a + b) ⋅ (b ⋅ (-1)) = ((a ⋅ b) ⋅ (-1)) + ((b ⋅ b) ⋅ (-1)) |
Comments
Please log in to add comments